Associations between maternal depressive symptoms and selective serotonin reuptake inhibitor antidepressant treatment on internalising and anxiety behaviours in children: 12-year longitudinal study. Issue 2 (1st March 2023) - Hutchison, Sarah M.; Brain, Ursula; Grunau, Ruth E.; Kuzeljevic, Boris; Irvine, Mike; Mâsse, Louise C.; Oberlander, Tim F.
Abstract : Background: Prenatal selective serotonin reuptake inhibitor (SSRI) antidepressant exposure is associated with increased internalising and anxious behaviours in young children; whether this continues into early adolescence is unknown. Also, it is not well established whether it is the in utero exposure to SSRIs or the underlying maternal mood that contributes more to these associations. Aims: To examine associations between maternal depressive symptoms, prenatal SSRI antidepressant treatment and internalising and anxiety behaviours from childhood into pre-adolescence. Method: From a prospective longitudinal cohort, measures of maternal depressive symptoms and SSRI use and child outcomes ( n = 191 births) were obtained from the second trimester to 12 years. Maternal reports of internalising and anxiety behaviours in children were obtained at 3, 6 and 12 years. Results: Multilevel mixed-effects models revealed that maternal depressed mood at the third trimester assessment, not prenatal SSRI exposure, was associated with longitudinal patterns of higher levels of internalising and anxiety behaviours across childhood from 3 to 12 years of age. At each age, hierarchical regressions showed that maternal mood at the third trimester, compared with current maternal depression or prenatal SSRI exposure, explained a greater proportion of the variance in internalising and anxiety behaviours. Conclusions: Even with prenatal SSRI treatment, maternal depressed mood during the third trimester still had an enduring effect as it was associated with increased levels of internalising and anxiety behaviours across childhood and into early adolescence. Importantly, we found no evidence of a 'main effect' association between prenatal SSRI exposure and internalising and anxiety behaviours in children.